A Comparative Study to Examine the Effects of Topical Vinpocetine and Tacrolimus on Induced Atopic Dermatitis in Mice. - Habbas, Al hasan Haitham; Abu Raghif, Ahmed (Tikrit Journal of Pharmaceutical Sciences, 2023)
Background: Atopic dermatitis (AD) is a persistent and recurring inflammatory skin disorder distinguished by parched skin and severe itching. The pathogenesis of AD involves increased production of specific cytokines, such as Interlukin-4 (IL-4) and Interlukin-13 (IL-13), which are associated with the T helper 2 pathway. However, prolonged use of the current glucocorticoids and calcineurin inhibitors medications can lead to adverse effects. Aim of the study: To assess the efficiency of topical Vinpocetine and Tacrolimus in treating an induced atopic dermatitis mice model. Methods: Five sets of fifty male Albino mice, were randomly selected. One-chloro-2,4-dinitrobenzene (DNCB) was applied to the dorsal (back) skin of forty mice to cause atopic dermatitis. Ten control healthy mice were placed in Group I, ten mice with atopic dermatitis were placed in Group II; neither group received any treatment. Group III consists of 10 mice that received tacrolimus 0.1% ointment, group IV was administered a topical ointment comprising 5% Vinpocetine and lastly, group V underwent a vehicle ointment. Severity was assessed visually, IL-4 and IL-13 were measured by immunohistochemistry, in addition to general histopathological evaluation as well as examining WBCs. Results: The groups treated with Vinpocetine 5%, and Tacrolimus all had significantly lower levels of WBC counts, decreased IL-4 and IL-13 staining according to immunohistochemistry and lower histopathological scores. Vinpocetine 5% and tacrolimus treatment also showed a statistically significant reduction in hyperkeratosis and inflammation among the studied groups (P<0.001). Conclusions Topical Vinpocetine 5% ointment, and tacrolimus 0.1% were effective in the treatment of induced AD mouse model through the improvement of histopathological changes and their ability to decrease IL-4 and IL-13, Vinpocetine were effective in the treatment of induced AD. Keywords: Atopic dermatitis, Tacrolimus, Topical, Vinpocetine.